PRINSIP MAṢLAḤAH ATURAN PEMASANGAN ‘POLISI TIDUR’ DI JALAN PEMUKIMAN MENURUT HUKUM ISLAM DAN HUKUM POSITIF - Cahayaningsih, Ica Putri; Hamidah, Tutik (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2024)
The installation of speed bumps must be carried out by units/institutions determined in accordance with Minister of Transportation Regulation Number 82 of 2018, so that they do not cause accidents and have negative consequences for road users. The aim of this research is to find out the law on installing speed bumps on public roads, both in terms of positive law and Islamic law. Apart from that, it is also to find out the sanctions obtained from installing speed bumps that do not comply with the regulations. This research is library research. This research was carried out by searching, reading, collecting and analyzing several sources related to the existing problem. The results of this research are that the basis for installing speed bumps is regulated in Law No. 14 of 2021, Amendments to Regulation of the Minister of Transportation No. 82 of 2018 concerning Road User Control and Safety Devices. These regulations explain the standards for installing speed bumps. Meanwhile, from an Islamic legal perspective, installing speed bumps can be considered a preventive measure to regulate vehicle speed and maintain the safety of drivers and pedestrians in certain locations. This is in line with the principle of maslahah (general goodness) in maintaining life and order.